Investigating TikTok as a learning tool for learning chemistry: a study among secondary school students in Malaysia / Nur Farha Shaafi ... [et al.] - Shaafi, Nur Farha; Mohd Yusof, Mohammad Mubarrak; Mohammad Khalipah, Nurul Nabilla; Mohd Hanif, Norhazly (Universiti Teknologi MARA Cawangan Kedah, 2023)
TikTok is a social media, video-based phone application, which enables creative and engaging videos that are rapidly growing in popularity. TikTok has been used to create fun, exciting, and engaging 15-60 second duration educational chemistry and science outreach videos. This study aims i.e., (i) to investigate the effectiveness of TikTok as a learning tool for learning chemistry among secondary school students in Malaysia, and (ii) to compare the effectiveness of TikTok and traditional mind-map technique in facilitating secondary school students’ learning chemistry and determine which approach is preferred by students. Non-random purposive sampling was used to select 40 participants from two different secondary schools, namely Sekolah Menengah Integrasi Sains Tahfiz, Cheras, Kuala Lumpur, and Sekolah Menengah Tinggi Sultan Salahuddin Abdul Aziz Shah, Sabak Bernam, Selangor. The instruments used were document and interview sessions. The results showed that the overall response to the survey was promising as most of the respondents gave positive feedback on the use of the TikTok application in their chemistry learning process. In this respect, the potential of TikTok to be used as a learning tool should be further explored since it enables the designing and delivering of creative and high-quality e-learning content.